Response of Tuberose to Integrated Nutrient Management - Kabir, AKMR; Iman, MH; Mondal, MMA; Chowdhury, S (Journal of Environmental Science and Natural Resources, 2012)
A field experiment was conducted at the farmer’s field of Sutiakhali, Mymensingh Sadar Upazilla, Mymensingh, during the period from April, 2009 to March, 2010 to investigate the effect of organic fertilizers along with half chemical fertilizers on the growth, bulb and flower yield of tuberose cv. single. The experiment consisted of four different sources of fertilizers viz., (i) recommended chemical fertilizers @ 400, 300, 300 and 100 kg ha-1 of urea, TSP, MP and gypsum, respectively; (ii) vermicompost @ 5 t ha-1 along with half of chemical fertilizers; (iii) poultry litter @ 20 t ha-1 along with half of chemical fertilizers and (iv) cowdung @ 20 t ha-1 along with half of chemical fertilizers. The experiment was laid out in a randomized complete block design with three replications. Results revealed that plant height, leaf number plant-1, leaf length and breadth and number of side shoots plant-1, bulb production plant-1, bulb length, bulb diameter and bulb yield both per plant and per hectare, rachis length, spike length and diameter, number of florets spike-1 and flower yield both per spike and per hectare were greater in organic fertilizers along with half chemical fertilizers than absolute use of chemical fertilizers. The highest bulb and flower yield both per plant and per hectare were recorded in poultry manures followed by cowdung. The bulb and flower yields were higher in poultry manures might be due to increased side shoots number, bulb size and flowers plant-1. In contrast, the lowest bulb and flower yields were recorded in chemical fertilizers due to production of fewer side bulb and flowers plant-1. DOI: http://dx.doi.org/10.3329/jesnr.v4i2.10135 J. Environ. Sci. & Natural Resources, 4(2): 55-59, 2011